2022
DOI: 10.1186/s40623-022-01642-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for presence of a global quasi-resonant mode of oscillations during high-intensity long-duration continuous AE activity (HILDCAA) events

Abstract: The responses of two High-Intensity Long-Duration Continuous AE Activity (HILDCAA) events are investigated using solar wind observations at L1, magnetospheric measurements at geosynchronous orbit, and changes in the global ionosphere. This study provides evidence of the existence of quasi-periodic oscillations (1.5–2 h) in the ionospheric electric field over low latitudes, total electron content at high latitudes, the magnetic field over the globe, energetic electron flux and magnetic field at geosynchronous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Tsurutani et al (2004) concluded that they were not substorms, and suggested instead that intensifications of the westwards electrojet by prompt penetration of interplanetary electric fields could be the cause. Rout et al (2022) also concluded that HILDCAAs were not directly related to substorms but produced by the excitation of a global perturbation with a "quasi-resonant frequency" of order 1.5-2 hr. On the other hand, Kim et al (2008) found that energetic particle injections at geosynchronous orbit during HILDCAAs were well-aligned with substorm onsets seen in global auroral imagery, so deduced that most of these activations were indeed substorms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsurutani et al (2004) concluded that they were not substorms, and suggested instead that intensifications of the westwards electrojet by prompt penetration of interplanetary electric fields could be the cause. Rout et al (2022) also concluded that HILDCAAs were not directly related to substorms but produced by the excitation of a global perturbation with a "quasi-resonant frequency" of order 1.5-2 hr. On the other hand, Kim et al (2008) found that energetic particle injections at geosynchronous orbit during HILDCAAs were well-aligned with substorm onsets seen in global auroral imagery, so deduced that most of these activations were indeed substorms.…”
Section: Discussionmentioning
confidence: 99%
“…The IMF within the HSSs undergoes Alfvénic fluctuations on a variety of timescales ranging from minutes to hours (e.g., Rout et al., 2022). The superposition of long and short timescales results in variability within Φ D which differs for each HILDCAA event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they reported that the magnetotail responds to IMF fluctuations during HILDCAA. Rout et al (2022) used the wavelet transform and cross-spectrum analysis to examine the responses of two HILDCAA events to solar wind observation. It was found that the quasi-periodic oscillation of 1.5-2 hr in the interplanetary electric field is the most effective parameter that controls the solar wind-magnetosphere-Ionosphere coupling process during HILDCAA events.…”
mentioning
confidence: 99%
“…caused by PPEF, DDEF, disturbed thermospheric winds, and compositional changes in low to midlatitude regions during HILDCAA (daSilva et al, 2020;Koga et al, 2011;Matamba & Habarulema, 2021;Rout et al, 2022;Silva et al…”
mentioning
confidence: 99%